The Influence of Entrepreneurial Learning, Internship Experience and Informal Education on Entrepreneurial Readiness Through Entrepreneurial Literacy: (Study On Vocational School Students In Pangkep District) - Jafar, Muhammad; Ramli, Anwar; Rakib, Muhammad; Azis, Muhammad (Lafadz Jaya Publisher, 2023)
The magnitude of the opportunity for schools to shape students' entrepreneurial readiness in vocational schools is directly proportional to the output of students' entrepreneurial readiness which carries risks and is inherent in the entrepreneurial profession itself. The fact is that vocational school students cannot compete and are not ready to use it in the world of work, even though they are prepared to be able to immediately enter the business world. This phenomenon shows that the behavioral perspective which focuses on student behavior is unable to reconstruct vocational school students' entrepreneurial knowledge as literacy to provide knowledge for entrepreneurial readiness. Therefore, the aim of this research is to test and analyze the influence of entrepreneurial learning, internship experience and informal education on entrepreneurial readiness through entrepreneurial literacy as a study on vocational school students in Pangkep Regency.This research is quantitative research that emphasizes analysis based on data and numbers and relies on the conclusion of the results on an error probability of rejecting the null hypothesis (Ho) which is built on a strong theory. Data was obtained through observation, questionnaires and documentation with a population of 2,121 students using probabilistic sampling techniques. The research sample was 337 students. Next, the data were analyzed descriptively and inferentially using structural equation modeling techniques to test the 8 hypotheses in the research. The results of the research show that the variables of entrepreneurial learning and internship experience have a positive and significant effect on students' entrepreneurial literacy and entrepreneurial readiness. However, informal education does not have a positive and significant effect on literacy. entrepreneurship and students' entrepreneurial readiness. In line with this, entrepreneurial literacy can mediate entrepreneurial learning, internship experience, informal education and entrepreneurial literacy towards the entrepreneurial readiness of Vocational High School (SMK) students in Pangkep Regency.